Effect of Designed Teaching Protocol Regarding Patients' Safety after Cardiac Catheterization on Nurses' Performance and Patients’ Incidence of Vascular Complications (International Journal of Studies in Nursing, 2019)
Background: Vascular access-site complications are an important cause of morbidity and mortality, which is related mainly to vascular percutaneous intervention procedures and requires safe and standardized care policies, as well as qualified and skilled health provider to obtain good outcome of management. Aim of the study: to investigate the effect of designed teaching protocol regarding patients’ safety after cardiac catheterization on nurses’ performance and patients’ incidence of vascular complications. Aquasi-experimental design was used to conduct the current study in cardiac catheterization and coronary care units at Benha University Hospital during the period from beginning of April 2018 till beginning of October 2018. Subjects: A sample of convenience of 50 nurses who are willing to participate in the study, and patients who admitted for performing cardiac catheterization were 071 patients recruited according to the study formula based on the total number admitted to the study settings during 2017. Tools: Two tools were utilized for data collection, (Ι) Structured interviewing questionnaire for nurses, (II) Patients’ assessment sheet. Results: Showed that nurses’ level of knowledge and practice post implementing the designed teaching protocol was higher than pre implementation, with a significant correlation between nurses’ knowledge and practice(p=